Israel : as a phoenix ascending - Penkower, Monty Noam, 1942- (Touro University Press books., 2021)
"The chapters in this volume examine a few facets in the drama of how the beleaguered Jewish people, as a phoenix ascending of ancient legend, achieved national self-determination in the reborn State of Israel within three years of the end of World War II and of the Holocaust. They include the pivotal 1946 World Zionist Congress, the contributions of Jacob Robinson and Clark M. Eichelberger to Israel's sovereign renewal, American Jewry's crusade to save a Jewish state, the effort to create a truce and trusteeship for Palestine, and Judah Magnes's final attempt to create a federated state there. Joining extensive archival research and a lucid prose, Professor Monty Noam Penkower again displays a definitive mastery of his craft"--